Menjembatani Penelitian Kualitatif dan Kuantitatif Irfan Sanusi - Irfan Sanusi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2009)
The quantitative method of research inspired by August Comte in his Philosophy of Positivism, is contradictory with the qualitative method of research which is one of the methods elaborated and derived from  rationalism. I suggest that quantitative research  models– descriptive model, correlation, experiment and quasi-experiment – should be placed on the grand theory as well as the the social context, or to follow the logic of qualitative method, so that  research invention is inseparable from the grand situation. In light of this view, I  suggest that the  two contradictory methods of research be combined.